PENGARUH SISTEM INFORMASI MANAJEMEN DAN LINGKUNGAN KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT. INHIL SARIMAS KELAPA RUMBAI JAYA KABUPATEN INDRAGIRI HILIR - Heriasman, Heriasman (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This research at PT. Inhil Sarimas Kelapa Rumbai Jaya Regency of Indragiri Hilir. The purpose of this study is to determine the effect of management information systems and work environment on employee work effectiveness at PT. Inhil Sarimas Kelapa Rumbai Jaya Regency of Indragiri Hilir. This research used quantitative methods, namely research that illustrates the influence of management information systems and work environment on the effectiveness of employee work at PT. Inhil Sarimas Kelapa Rumbai Jaya Regency of Indragiri Hilir. To anyzed the data, this research used multiple regression, correlation coefficients, and Hypothesis testing which will be assisted by using SPSS version 21. From the results of the study show that management information system variables and work environment together have a significant influence on employee work effectiveness, management information systems have a significant effect on employee work effectiveness. and The work environment has a significant effect on employee work effectiveness at PT. Inhil Sarimas Kelapa Rumbai Jaya Regency of Indragiri Hilir